Pengaruh Partikel Nano Abu Vulkanik dan Batuan Fosfat terhadap Muatan Variable dan Kemasaman Andisol - Anne Yuliana; Mahfud Arifin; Nenny Nurlaeny (Agrikultura, 2017)
ABSTRACTThe effect of particle nano volcanic ash and rock phosphate on variable charge or zero point of charge (pH0) and soil acidity of AndisolsThis experiment aimed to find out the effect of particle nano volcanic ash and rock phosphate on variable charge or zero point of charge (pH0) and soil acidity of Andisols from Ciater Subang-West Java. This experiment was conducted from October 2016 to March 2017 at Soil fertility and Plant Nutrition Laboratory and Physic Soil Laboratory of Soil Science and Land Resources Department, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The experiment was arranged in Completely Randomized Design consisted of two factors. The first factor was particle of nano volcanic ash consisted of 4 levels. The second factor was particle of nano rock phosphate consisted of 4 levels and 3 replications. The results showed that there was no interaction between nano particle of volcanic ash and rock on zero point of charge (pH0), but there was interaction effect on pH-H2O. Combination of 2.5% nano particle of volcanic ash and 0% nano particle of rock phosphate could reduce the value of zero point of charge (pH0) as much 28.57%. Combination of 5% volcanic ash nano particle and 7.5% rock phosphate nano particle dosage was the best treatment and could increase the value of soil acidity or pH-H2O until 20.36%.Keywords: Andisol, pHο, Rock phosphate, Volcanic ashABSTRAKTujuan dari penelitian ini adalah untuk mengetahui pengaruh partikel nano abu vulkanik dan batuan fosfat terhadap muatan variable atau titik muatan nol (pH0) dan kemasaman tanah Andisols Ciater Subang-Jawa Barat. Penelitian ini dilaksanakan pada bulan Oktober 2016 sampai dengan Maret 2017 di Laboratorium Kesuburan Tanah dan Nutrisi Tanaman serta Laboratorium Fisika Tanah Departemen Ilmu Tanah dan Sumber Daya Lahan, Fakultas Pertanian, Universitas Padjadjaran, Jatinangor. Penelitian ini menggunakan Rancangan Acak Lengkap pola faktorial dengan dua faktor. Faktor pertama adalah partikel nano abu vulkanik yang terdiri dari 4 taraf. Faktor kedua adalah partikel nano batuan fosfat yang terdiri dari 4 taraf, diulang sebanyak 3 kali. Hasil penelitian menunjukkan bahwa tidak terjadi interaksi antara partikel nano abu vulkanik dan batuan fosfat terhadap titik muatan nol (pH0) namun terjadi interaksi antara kedua perlakuan tersebut terhadap kemasaman tanah (pH-H2O). Komposisi dosis yang paling baik dalam menurunkan pH0 adalah 2,5% partikel nano abu vulkanik dan 0% partikel nano batuan fosfat yaitu sebesar 28,57%, sedangkan komposisi dosis yang paling baik dalam meningkatkan pH-H2O adalah 5% partikel nano abu vulkanik dan 7,5% partikel nano batuan fosfat yaitu sebesar 20,36%.Kata Kunci: Abu vulkanik, Andisol, Batuan fosfat, pH0